Role of Vidangadi Kwatha in Madhumeha (Diabetes Mellitus Type II) - Premlata; B, Ram; Vimlesh; Choudhary, Sachin; Khachariya, Jitendra (Archives of Clinical and Medical Case Reports, 2021)
Diabetes mellitus (DM) refers to a group of common metabolic disorders that share the phenotype of hyperglycaemia. The two broad categories of DM are designed type 1 and type 2. Type 1 diabetes is the result of complete or near-total insulin deficiency. Type 2 DM is a heterogeneous group of disorders characterized by variable degrees of insulin resis-tance, impaired insulin secretion, and increased glucose production. Here a case of newly diagnosed type 2 diabetes mellitus in a patient who underwent 3 follow up of Vidangadi Kwatha delivered in 3 months is reported. After treatment, the patient’s fasting blood glucose and post plasma blood glucose levels, as well as haemoglobin A1C level, were decreased. Further-more, no adverse effects were observed. The finding in this clinical study are encouraging and provide evidence supporting the effectiveness of Vidangadi Kwatha in reducing type 2 diabetes melli-tus in a patient.